In-vitro Compatibility of Some Native Isolates of Trichoderma spp. with Commonly used Pesticides - Budha, C B; Shrestha, S M; Manandhar, H K; Baidya, S (Journal of the Plant Protection Society, 2022)
Trichoderma is an effective bio-control agent against a wide range of disease-causing pathogens of various crops and potential to be integrated into the disease management program. The study was conducted to find out the compatible pesticide/s with Trichoderma for integrated pest management (IPM). This study includes in-vitro evaluation of four chemical fungicides (carbendazim, copper-oxychloride, captan and tebuconazole + sulphur), three chemical insecticides (malathion, imidachlorpid and chlorpyriphos + cypermethrin) and one botanical insecticide (azadirachtin) for compatibility with seven different native isolates and two known species of Trichoderma through poisoned food technique. Copper-oxychloride was found compatible with all the tested isolates. In contrast, carbendazim and tebuconazole + sulphur were found incompatible. The insecticides, malathion, imidachlorpid, chlorpyriphos + cypermethrin, azadirachtin and the fungicide, captan showed some degree of compatibility. It is concluded that the tested Trichoderma isolates and the given species could be used together in combination with the given compatible fungicide such as copper-oxychloride and the given insecticides. These results would be helpful to set out the possibility of combining Trichoderma spp. as a biocontrol agent with pesticides to be used through IPM approach.